2010
DOI: 10.1021/es100526g
|View full text |Cite
|
Sign up to set email alerts
|

Copper Recovery Combined with Electricity Production in a Microbial Fuel Cell

Abstract: A metallurgical microbial fuel cell (MFC) is an attractive alternative for recovery of copper from copper containing waste streams, as the metal is recovered in its metallic form at the cathode, while the energy for metal reduction can be obtained from oxidation of organic materials at the anode with possible additional production of electricity. We studied the recovery of copper in an MFC using a bipolar membrane as a pH separator. Under anaerobic conditions, the maximum power density was 0.43 W/m(2) at a cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(158 citation statements)
references
References 20 publications
6
151
1
Order By: Relevance
“…Figure 2 shows the current density produced with acetate and hydrogen gas as an electron donor at different hydrogen gas inflow rates and anolyte recirculation speed. For acetate, the maximum current density was 6.8 A m ‐ 2 at an anode potential of –0.30 V, which is comparable with values reported in the literature 3, 4, 21. For hydrogen gas as electron donor supplied at 3 mL min ‐1 , the maximum current density was 1.5 A m ‐ 2 at –0.20 V anode potential, for the highest anolyte recirculation speed of 200 mL min ‐1 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Figure 2 shows the current density produced with acetate and hydrogen gas as an electron donor at different hydrogen gas inflow rates and anolyte recirculation speed. For acetate, the maximum current density was 6.8 A m ‐ 2 at an anode potential of –0.30 V, which is comparable with values reported in the literature 3, 4, 21. For hydrogen gas as electron donor supplied at 3 mL min ‐1 , the maximum current density was 1.5 A m ‐ 2 at –0.20 V anode potential, for the highest anolyte recirculation speed of 200 mL min ‐1 .…”
Section: Resultssupporting
confidence: 88%
“…In practice, industrial copper plating requires 2.7 kWh kg ‐1 Cu when water is used as electron donor due to a high overpotential for this reaction 1, 2. Previously it has been shown that bioelectrochemical systems (BESs) can be used for the recovery of metals, using electron donors present in wastewater such as acetate 3. The oxidation of organics such as acetate, gives an energetic advantage over water oxidation and even results in power production combined with copper recovery.…”
Section: Introductionmentioning
confidence: 99%
“…23,25,26 . Ter Heijne et al (2010) were the first to use a BES, with acetate as an electron donor, and Cu 2+ as the electrode acceptor in the cathode. They showed the possibility to remove copper from wastewater and production of pure plated copper, in combination with electricity production (Figure 1.2).…”
Section: Bioelectrochemical Systems; State-of-the-artmentioning
confidence: 99%
“…They showed the possibility to remove copper from wastewater and production of pure plated copper, in combination with electricity production (Figure 1.2). The novelty of the application of BES for the recovery of metal waste was that this provides an energy-efficient alternative to conventional electrowinning processes, because the electron donor (wastewater) provides (part of) the energy to drive the reduction reaction [27][28][29][30][31][32] .…”
Section: Bioelectrochemical Systems; State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation